2015
DOI: 10.3168/jds.2014-9223
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of parturition in Holstein dairy cattle using electronic data loggers

Abstract: The objective of the present study was to assess the effect of parturition on behavioral activity [steps, standing time, lying time, lying bouts (LB), and duration of LB] 4 d before calving using electronic data loggers. Animals (n=132) from 3 herds were housed in similar freestall barns using a prepartum pen 21 d before the expected calving date and were moved into a contiguous individual maternity pen for parturition. Electronic data loggers were placed on a hind leg of prepartum heifers (heifers, n=33) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 29 publications
4
48
1
3
Order By: Relevance
“…Previous studies have observed changes in feeding and resting behaviour determined by sensors in the last 24 hours before calving (Bucher and Sundrum, 2014, Clark, et al, 2015, Schirmann, et al, 2013, Titler, et al, 2015. No such effects were observed in the data of the sensor parameters "feeding" and "not active" in the current study.…”
Section: Discussioncontrasting
confidence: 41%
See 4 more Smart Citations
“…Previous studies have observed changes in feeding and resting behaviour determined by sensors in the last 24 hours before calving (Bucher and Sundrum, 2014, Clark, et al, 2015, Schirmann, et al, 2013, Titler, et al, 2015. No such effects were observed in the data of the sensor parameters "feeding" and "not active" in the current study.…”
Section: Discussioncontrasting
confidence: 41%
“…It should be noted that these studies generated alerts every two hours instead of every hour and that reduces the total number of alerts including the false positive alerts. Other studies have also reported activity to increase during the 24 hours before calving (Clark, et al, 2015, Miedema, et al, 2011b, Saint-Dizier and Chastant-Maillard, 2015, Titler, et al, 2015. For "temperature", a decrease of about 3°C was observed during the hour in which calving started, whereas other studies have reported decreases in the range of 0.2-0.5 °C (Burfeind, et al, 2011, Ouellet, et al, 2016.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations